Comparative study on joining quality of electromagnetic driven self-piecing riveting, adhesive and hybrid joints for Al/steel structure. (July 2021) - Jiang, Hao; Liao, Yuxuan; Gao, Song; Li, Guangyao; Cui, Junjia
Abstract: riveted–adhesive hybrid joining technique is suitable for joining dissimilar material due to excellent performance and tightness of the joint. In this paper, electromagnetic self-piecing riveted–adhesive hybrid joining method was proposed to join Al/steel structure. The mechanical properties and failure behavior of electromagnetic self-piecing riveting, adhesive and its hybrid joints were compared. The shear tests were conducted, and digital image correlation (DIC) technique was employed to analyze the strain of the sheets. The typical failure fracture was observed to reveal the failure mechanism. The results showed that the peak load of the hybrid joint was 177.3% larger than that of the riveted joint, and the energy absorption of the hybrid joint was 360.0% and 47.9% higher than that of the riveted and bonded joint respectively. The failure process of electromagnetic self-piecing riveted–bonded hybrid joint could be divided into two parts: adhesive failure firstly and then rivet failure. The rivet in hybrid joint after adhesive failure could still suffer a certain amount of load, so that suddenly complete failure was not easy to happen. This indicated that the hybrid joint had better reliability and security. In general, the combination of electromagnetic self-piecing riveting and adhesive bonding could produce beneficial coupling effect. Highlights: Electromagnetic self-piecing riveted–adhesive hybrid joining technique was proposed to join steel/Al structure. The mechanical properties of the electromagnetic self-piecing riveting, adhesive and hybrid joints were compared. The failure mechanism of the electromagnetic self-piecing riveting, adhesive and hybrid joints was analyzed.